HOW MINIMUM COMPETENCY–ORIENTED GEOMETRY INSTRUCTION SUPPORTS STUDENTS’ MATHEMATICAL LITERACY: INSIGHTS FROM A DESIGN-BASED STUDY - Muzdalipah, Ipah; Hidayat, Edi; Rustina, Ratna; Kurniasih, Dwi (Journal of Authentic Research on Mathematics Education (JARME), 2026)
This study aimed to develop Minimum Competency Assessment (MCA)-based geometry instructional materials to support junior high school students’ mathematical literacy, particularly in the formulate–employ–interpret process. The research employed a Research and Development (RD) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The analysis stage revealed learning gaps, including the dominance of procedural approaches, limited use of visual and contextual media, and students’ difficulties in interpreting contextual geometry problems. The instructional materials were developed with contextual introductions, concept visualizations, AKM-based tasks, reflection activities, and geometric nets. Product validity was assessed by a content expert and a media expert, covering content and objective quality, instructional quality, and technical quality, with an average score of 74.3% (valid category). Practicality testing involving 25 eighth-grade students showed percentages ranging from 77% to 79%, indicating that the instructional materials are feasible and practical for classroom use. Further studies are recommended to examine effectiveness through experimental designs and to expand the development of interactive media. Copyright © 2021University of Siliwangi. All rights reserved.